Encyclopedia of British writers, 1800 to the present [ 20th century and beyond - Karbiener, Karen , 1965-; Stade, George (Gale virtual reference library, 2009)
Profiles the finest British poets, novelists, playwrights, essayists, and other writers of the 19th, 20th, and 21st centuries, including essential details about the author's life and work and suggestions for further reading. Writers from Ireland and nations of the British Commonwealth are also included